Influence of Competence and Compensation on the Performance of Employees of Bandung Saung Kabayan Restaurant - Aprilyani, Rani; Waluya, Bagja; Ridwanudin, Oce (Gastronomy Tourism Journal, 2019)
Employee performance from the most vulnerable literature occurs in the restaurant Saung Kabayan Bandung. As low as employees' knowledge and initiative can affect performance. Therefore, improving performance needs to pay attention to competency and compensation factors. This study aims to determine the effect of 1) Competence on employee performance; 2) Compensation for employee performance, and 3) Competence and compensation for employee performance. The dimensions of competency variables (X1) consistency of motives, traits, self-concept, knowledge and skills and; compensation variable (X2) consisting of salary and wages, incentives, benefits, and adequate facilities and; Employee performance variable (Y) consists of work quality, timeliness, initiative, ability, and communication. This research uses a descriptive and verification approach. The method used is an explanatory survey with a sample of 56 respondents (saturated sample). The data analysis technique used is multiple linear regression. The results showed that competence and compensation had a positive and significant effect both partially and simultaneously on employee performance at Saung Kabayan Restaurant Bandung with a coefficient value of 67.5%. Based on research results, competencies need to be improved through training activities, but competencies need to be balanced with fair compensation so as to improve employee performance.